Effects of Phenolic Plant Extracts on Biofilm Formation by Klebsiella pneumoniae Isolated from Urinary Tract Infections - Alattar, Nagham Shakir; Emran, Faiza Kadhim; Oleiwi, Sanaa Rahman (Iraqi Journal of Science, 2024)
Ten isolates of Klebsiella pneumoniae, seven isolates of Pseudomonas aeruginosa and nine isolates of Staphylococcus aureus, were obtained from 100 urine samples collected from Baghdad hospitals. All isolates were identified biochemically and confirmed by using VITEK 2 and were then tested for their susceptibility towards 6 antibiotics and for phenolic extracts of Thymus vulgaris and Cinnamomum cassia. All bacteria were greatly affected by T. vulgaris, especially K. pneumoniae. Viable count was performed, it was noted that the number of bacterial cells reduced from 1×108 CFU to 1.2× 103, 2×105 and 1.8×106CFU of K. pneumoniae, P. aeruginosa and S. aureus respectively. While C. cassiahad a slight effect on them. K. pneumoniae isolates which were affected by phenolic extract more than the other bacteria under study and at the same time were resistant to more than one type of tested antibiotics. These isolates were taken to detect their ability to form biofilm by using Congo red as screening method for it. The results showed that all isolates produced biofilms. Also, by using microtiter plate method, the results confirmed that all isolates produced biofilm where 7 isolates were strong biofilm producers and 3 were moderate. The strongest isolate was taken to study the effect of T. vulgaris and C. cassia phenolic extract on its biofilm formation by using microtiter plate method with two concentrations (20 and 40 ml/L). The results showed that biofilm reduction was 45% and 73% for T. vulgaris and that for C. cassiait was 15% and 20% after using 20 and 40 ml/L respectively.